The Assessment of Health Risk from Heavy Metals with Water Indices for Irrigation and the Portability of Munzur Stream: A Case Study of the Ovacık Area (Ramsar Site), Türkiye - Kutlu Banu; Sarıgül Ali (Oceanological and Hydrobiological Studies)
Surface water samples from the area of Munzur Stream in Türkiye (a Ramsar site) were evaluated for their suitability for irrigation and drinking purposes using different water quality indices. The human health risks were assessed as well. The study was conducted over a period of 24 months from January 2019 to December 2021 by taking samples from nine stations every month in order to determine the water quality of Munzur Stream, located in Tunceli. According to the results, Munzur Stream is in good condition in terms of the quality of drinking water and irrigation water. The concentrations of heavy metals such as Cu, Ni, Fe and Hg were high, though the water quality parameter according to Türkiye Ministry of Forestry and Water Affairs Surface Water Quality Regulations (TSWQR) was significantly lower than the permitted limits. In Munzur Stream, the irrigation water for all stations was reported to be excellent, good and suitable in terms of SAR, Na% and MH, respectively. The principal component analysis data formed the four principal components, explaining 98.22% of the total variance. The sources of pollution in this area include the rock types of the basin, soil erosion, domestic waste water discharge and agricultural flow of inorganic fertilisers.